Carthamus tinctorius L. response to nano-silicon foliar treatment under organic and inorganic fertilizer application - Naser Sabaghnia; Mohsen Janmohammadi (Acta Agriculturae Slovenica)
We studied the impacts of foliar application of nano-silicon in combination with various fertilizer treatments (both organic and chemical) on the yield and yield components of safflower in an upland semi-arid environment in Maragheh, Iran. The trial evaluated the application of 0.0 and 20 mM nano-silicon in conjunction with different fertilizer treatments, including a control, 90 kg ha-1 NPK, and organic fertilizer at rates of 15 and 30 t ha-1. Analysis using a principal components approach revealed that the first two principal components of the treatment by trait biplot model explained 66% and 22% of the observed variability, respectively. Positive correlations were observed among straw yield, achene yield, and harvest index, as well as among capitula number per plant, seed per subsidiary capitulum, and the number of highest capitula. The combination of NPK with 20 mM nano-silicon resulted in superior yield performance, whereas the combination of 30 t ha-1 organic fertilizer with 20 mM nano-silicon exhibited enhanced yield components. Plant height emerged as the most representative trait, with high discrimination potential. Treatment with 30 t ha-1 organic fertilizer, combined with both 0.0 and 20 mM nano-silicon, was identified as the optimal treatment combination for discriminating among various safflower traits.